ANALISIS ALASAN GURU BELUM MEMANFAATKAN TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE ) SECARA OPTIMAL DALAM PEMBELAJARAN DI TK TAT TWAM ASI - Elisabeth Mbadhi; Sartika Kale; Credo G. Betty; Theodorina N. Seran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal implementation of Technological Pedagogical Content Knowledge (TPACK) in the learning process at Tat Twam Asi Kindergarten, Kupang City. The purpose of this study was to identify the reasons why teachers have not utilized TPACK optimally in classroom instruction. This study employed a qualitative method with a descriptive approach. Primary data were collected through semi-structured interviews with teachers of Classes B1 and B2, while secondary data were obtained from the principal and relevant literature. The trustworthiness of the data was ensured through source triangulation. Data were analyzed using four stages: data collection, data reduction, data presentation, and conclusion drawing. The findings revealed three main factors contributing to the suboptimal utilization of TPACK at Tat Twam Asi Kindergarten, Kupang City. First, teachers had limited understanding of how to integrate technology with learning content and pedagogical strategies, which was influenced by age-related factors that slowed their adaptation to technological developments. Second, teachers received limited training, and the training provided was predominantly theoretical without continuous mentoring. Third, technological facilities were inadequate, including limited hardware and software, as well as unstable internet access. This study provides recommendations for schools to enhance the implementation of TPACK by improving technological infrastructure, providing continuous professional development, and offering ongoing mentoring in the use of educational technology. These efforts are expected to help teachers become more competent and confident in integrating technology, pedagogy, and content knowledge, thereby improving the quality of the learning process. Keywords: TPACK, PAUD learning, learning technology, teacher competency, technology-based learning, early childhood education.